Synthesis, characterization, anti-proliferative and wound healing activities of silver nanoparticles synthesized from Caulerpa scalpelliformis. (April 2019) - Manikandan, R.; Anjali, R.; Beulaja, M.; Prabhu, N.M.; Koodalingam, A.; Saiprasad, G.; Chitra, P.; Arumugam, M.
Graphical abstract: Highlights: Silver nanoparticles (AgNPs) were synthesized from Caulerpa scalpelliformis and characterized. AgNPs induced apoptosis of MCF-7 by up regulating caspase 3/9 proteins. AgNPs showed anticancer activity by up regulating Bax and down regulating Bcl-2 mRNAs expression. AgNPs promoted skin would healing. Abstract: Green synthesis of silver nanoparticles is gaining momentum to avoid use of chemicals thus making eco-friendly approach. In continuation of our efforts to find effective alternative to chemical drugs, we have reported the C. scalpelliformis mediated synthesis of silver nanoparticles with biomedical properties. The green synthesized AgNPs also exhibited potent wound healing property by enhancing wound closure in an experimental rat model. Furthermore, the synthesized AgNPs also showed cytotoxic effects against MCF-7 cells, as exposure 40 μg/ml of AgNPs resulted in 50% cell death. This observed activity is mediated through modulating the mRNA level expression of Bax/ Bcl-2 and protein levels of caspase-3 and -9 in vitro . We are the first to report on anti-proliferative, pro-apoptotic effects and wound healing activity of AgNPs from C. scalpelliformis extract. The present study opens new avenues for use of AgNPs in various biomedical applications namely an anti-tumor agent and healing chronic and diabetic cutaneous wounds.